2014
DOI: 10.1002/jbm.a.35279
|View full text |Cite
|
Sign up to set email alerts
|

The scale-up of a tissue engineered porous hydroxyapatite polymer composite scaffold for use in bone repair: An ovine femoral condyle defect study

Abstract: The development of an osteogenic bone graft substitute has important practical and cost implications in many branches of medicine where bone regeneration is required. Previous in vitro and small animal (murine) in vivo studies highlighted a porous hydroxyapatite/poly (DL-lactic acid) composite scaffold in combination with skeletal stem cells (SSCs) as a potential bone graft substitute candidate. The aim of the current study was to scale up the bone cell-scaffold construct to large animals and examine the poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 24 publications
0
9
0
1
Order By: Relevance
“…Ex vivo XCT analysis of the integrated defect explants generally allows to distinguish the three phases that are present inside the defect, being newly formed bone, remaining biomaterials and soft tissues (van Lenthe & Müller, 2008;Sweedy et al, 2017;Witek et al, 2019). Apart from a qualitative information, the higher resolution that can be achieved with ex vivo XCT imaging of the explants compared to in vivo XCT, allows for a quantification not only of the bone volume formed within the defect site (Vila et al, 2014;Tayton et al, 2015;Kerckhofs et al, 2016;Sweedy et al, 2017;Kwon et al, 2018;Sharma et al, 2019) but also standard 3D morphometric parameters (i.e. trabecular thickness, trabecular spacing, trabecular number) of the newly formed bone at different time points (Howie et al, 2018;Sharma et al, 2019) and volume fraction of remaining biomaterial (Sweedy et al, 2017;Witek et al, 2019;Wu et al, 2019).…”
Section: Ex Vivo Analysis Of Bone Regenerationmentioning
confidence: 99%
See 2 more Smart Citations
“…Ex vivo XCT analysis of the integrated defect explants generally allows to distinguish the three phases that are present inside the defect, being newly formed bone, remaining biomaterials and soft tissues (van Lenthe & Müller, 2008;Sweedy et al, 2017;Witek et al, 2019). Apart from a qualitative information, the higher resolution that can be achieved with ex vivo XCT imaging of the explants compared to in vivo XCT, allows for a quantification not only of the bone volume formed within the defect site (Vila et al, 2014;Tayton et al, 2015;Kerckhofs et al, 2016;Sweedy et al, 2017;Kwon et al, 2018;Sharma et al, 2019) but also standard 3D morphometric parameters (i.e. trabecular thickness, trabecular spacing, trabecular number) of the newly formed bone at different time points (Howie et al, 2018;Sharma et al, 2019) and volume fraction of remaining biomaterial (Sweedy et al, 2017;Witek et al, 2019;Wu et al, 2019).…”
Section: Ex Vivo Analysis Of Bone Regenerationmentioning
confidence: 99%
“…However, little research has focused on the ex vivo mechanical competence of bone reconstructions after implantation of biomaterials. In particular, traditional mechanical tests such as indentation and microindentation at different locations through the defect areas have been used to measure the stress at failure (Tayton et al, 2015) and yield strength (Gauthier et al, 2005), respectively. Whereas indentation tests provided the mechanical strength of the healing defect size including both newly formed bone and remaining biomaterial (Tayton et al, 2015), microindentation allowed for the characterisation of the mechanical properties of the new regenerated bone tissue only (Gauthier et al, 2005).…”
Section: Biomechanical Xct Analysis Of Bone Regenerationmentioning
confidence: 99%
See 1 more Smart Citation
“…About 7 % (13 out of 175) of the studies showed little healing after the treatment with cellular scaffolds, with compromised efficacy ascribed to inappropriate choice of cells or scaffolds, poor conditions, or insufficient amount of cells. Notably, in eight studies using osteoblast cell sources, four showed no improvement to the healing, with two showing positive results only when BMP-2-transduced cell lines were used [35][36][37][38][39][40][41][42].…”
Section: Behavior Of Engineered Bone Grafts In Vivomentioning
confidence: 99%
“…Ainda, Niemeyer e colaboradores (2010) compararam as CTM de medula óssea com as CTM de tecido adiposo em associação com PRP para regeneração óssea da tíbia de ovelhas, observando um maior potencial regenerativo quando usadas CTM derivadas de medula óssea associadas ao PRP. A associação de PRP à CTM de medula óssea, separadamente ou associados a HA, em côndilos têmporo-mandibular (esquerdo e direito) de ovinos, revelou melhora da lesão quando as CTM estavam associadas ao biomaterial (CIOCCA et al, 2013), sendo o mesmo resultado obsevado por Tayton e colaboradores em defeitos bilaterais de condilos de ovinos (TAYTON et al, 2014).…”
Section: Discussionunclassified